2019
DOI: 10.1021/acs.jnatprod.8b00857
|View full text |Cite
|
Sign up to set email alerts
|

Isarubrolones Containing a Pyridooxazinium Unit from Streptomyces as Autophagy Activators

Abstract: Isarubrolones are bioactive polycyclic tropoloalkaloids from Streptomyces. Three new isarubrolones (2–4), together with the known isarubrolone C (1) and isatropolones A (5) and C (6, 3­(R)-hydroxyisatropolone A), were identified from Streptomyces sp. CPCC 204095. The structures of these compounds were determined using a combination of mass spectrometry, 1D and 2D NMR spectroscopy, and ECD. Compounds 3 and 4 feature a pyridooxazinium unit, which is rarely seen in natural products. Compound 6 could conjugate wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 13 publications
(23 reference statements)
0
14
0
Order By: Relevance
“…121 Rubterolones feature a tropolone moiety, a fused cyclopentanone ring, an O,C-condensated sugar and a highly substituted pyridine or pyridine inner salt moiety, and are structurally related to the recently identied rubrolone B 122 and isarubrolones. 123 Several biosynthetic studies and Fig. 9 Polyketides isolated from Actinomadura rubteroloni.…”
Section: Bacterial Symbiontsmentioning
confidence: 99%
“…121 Rubterolones feature a tropolone moiety, a fused cyclopentanone ring, an O,C-condensated sugar and a highly substituted pyridine or pyridine inner salt moiety, and are structurally related to the recently identied rubrolone B 122 and isarubrolones. 123 Several biosynthetic studies and Fig. 9 Polyketides isolated from Actinomadura rubteroloni.…”
Section: Bacterial Symbiontsmentioning
confidence: 99%
“…In the previous study, isarubrolone C (Figure 1A) was reported to activate autophagy in HepG2 cells. 2 Here, we determined whether this compound could degrade viral proteins by promoting autophagy flux in HepG2 cells. First, we constructed viral gene expression vectors including HBx, ZIKV-NS5, and HIV-RT genes, respectively, then together with HCV subreplicon (expressing HCV-CORE and -NS5B, constructed in our previous study) 18 were separately transfected into HepG2 cells and examined via Western blotting analysis (Figure 1B−E and Figure S1).…”
Section: Effect Of Isarubrolone C On Autophagy Flux and Viralmentioning
confidence: 99%
“…Isarubrolone C, together with its close analogues, was found to possess a biological activity of autophagic activation. Isarubrolone C triggered a complete autophagy process via promoting autophagosome formation and increasing the level of ATG7, ATG5, and ATG4b in HepG2 cells and showed very weak cytotoxic activity . However, isarubrolone C pharmacological effects are rarely studied and its antiviral activity has not been investigated to date.…”
mentioning
confidence: 99%
“…Rubrolone B, [6] the isarubrolone A [7] and the rubterolone A, [8] are a family of tropolone ring containing alkaloids that were recently isolated from a diverse array of actinomycetes (Figure 1A). These tropolonoids exhibit anti‐bacterial, anti‐fungal, and anti‐inflammatory properties, and have also been demonstrated to act as promising candidates for the induction of autophagy [9] . Further to the highly promising therapeutic utility of the isarubrolones, various aglycone subunits from this family can be used as probes for the covalent labeling and visualization of molecules containing and amine functionality [7] .…”
Section: Introductionmentioning
confidence: 99%
“…These tropolonoids exhibit anti-bacterial, antifungal, and anti-inflammatory properties, and have also been demonstrated to act as promising candidates for the induction of autophagy. [9] Further to the highly promising therapeutic utility of the isarubrolones, various aglycone subunits from this family can be used as probes for the covalent labeling and visualization of molecules containing and amine functionality. [7] In a previous study, we cloned and sequenced the rubrolone biosynthetic gene cluster (BGC) from Streptomyces sp.…”
Section: Introductionmentioning
confidence: 99%